Research on a Mixed Culture Technique of the White Rot Fungi Effect of Extracellular Lignin Peroxidase on Lignite Liquefaction - Shi, Kaiyi; Wang, Jun (Frontiers in Energy Research, 2019)
In order to improve the efficiency of lignite liquefaction, white rot fungi mixed culture technology was applied. Firstly, 15 fungi were used to liquefy Zhaotong lignite. The results show that there is a good linear relationship between liquefaction effect and lignin peroxidase (LiP). But the low activity of LiP is the barrier in real practice. Five strains with the highest LiP activity for combinatorial culture suggested that mixed strains culture is an effective way to improve LiP activity and liquefaction effect, and the average enzyme activity is 76.28 U/L. While the single strain is only 19.24 U/L. Besides, in 10 mixed strains cultures, four of them showing obvious synergy and the one with maximum enzyme activity has increased by 6.7 times. The analysis of lignite and liquefaction products by using 13C NMR shows that the aromatic carbon (fa) decreases, and the phenol or aromatic ether carbon (faP) and oxygen linked fatty carbon (falO) increase, which proves that LiP has undergone ring-opening, oxidation and other reactions in lignite liquefaction.